THE RELATIONSHIP OF THE VALUE OF SUBJECT ISLAMIC STUDIES WITH THE FORMATION OF THE SOCIAL ATTITUDES OF ELEMENTARY SCHOOL STUDENTS - Munawaroh, Munawaroh; Anwar, Mohammad Emnis (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2016)
Islamic education is a form of guidance and business forces opened to students, so that later, after the education to understand and practice the religion and make it a way of life. Islamic education is aimed at fostering religious man, the man who is able to implement the teachings of Islam with a good and perfect, so that is reflected in the attitudes and behavior of the overall actions of his life in order to achieve happiness of life on earth and the hereafter. This research will use quantitative research methods. Quantitative research is the definition, measurement and statistical objective, quantitative data to answer a number of questions about the survey to determine the frequency and percentage of their response. This research was conducted through observation, interview, questionnaire and sampling of the population who were subjected to experiments. Through observation, the authors could observe the situation of teaching and learning activities, the situation of social relationships in school environments particularly the interaction between teachers and students and between students and neighbors.